2016
DOI: 10.1111/boj.12427
|View full text |Cite
|
Sign up to set email alerts
|

Floral specialization for different pollinators and divergent use of the same pollinator among co-occurringImpatiensspecies (Balsaminaceae) from Southeast Asia

Abstract: Floral variation among closely related species is thought to often reflect differences in pollination systems. Flowers of the large genus Impatiens are characterized by extensive variation in colour, shape and size and in anther and stigma positioning, but studies of their pollination ecology are scarce and most lack a comparative context. Consequently, the function of floral diversity in Impatiens remains enigmatic. This study documents floral variation and pollination of seven co‐occurring Impatiens spp. in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Since pollinators tend to visit nearby plant species, spatially aggregated co‐flowering species are likely to experience stronger competition for pollinators and potentially suffer higher pollen loss and fitness decrease due to heterospecific pollen transfer (Fang & Huang, ; van der Kooi et al., ). Adaptations to minimize competition and pollen loss may include all those changes that reduce the sharing of pollinators, such as specialization on different pollinators (Kipling & Warren, ; Muchhala et al., ; Ruchisansakun, Tangtorwongsakul, Cozien, Smets, & van der Niet, ), shifts in flowering time (Devaux & Lande, ; Gleeson, ), a segregated spatial distribution (Kipling & Warren, ; Mosquin, ; Pleasants, ); or divergence in floral traits such as the anther position, which allows pollinator‐sharing species to avoid pollen loss by placing pollen on different parts of pollinators’ bodies (Ruchisansakun et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Since pollinators tend to visit nearby plant species, spatially aggregated co‐flowering species are likely to experience stronger competition for pollinators and potentially suffer higher pollen loss and fitness decrease due to heterospecific pollen transfer (Fang & Huang, ; van der Kooi et al., ). Adaptations to minimize competition and pollen loss may include all those changes that reduce the sharing of pollinators, such as specialization on different pollinators (Kipling & Warren, ; Muchhala et al., ; Ruchisansakun, Tangtorwongsakul, Cozien, Smets, & van der Niet, ), shifts in flowering time (Devaux & Lande, ; Gleeson, ), a segregated spatial distribution (Kipling & Warren, ; Mosquin, ; Pleasants, ); or divergence in floral traits such as the anther position, which allows pollinator‐sharing species to avoid pollen loss by placing pollen on different parts of pollinators’ bodies (Ruchisansakun et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a large floral chamber with a wide entrance are traits associated with bee pollination in Southeast Asian Impatiens (Ruchisansakun et al 2016). Based on the traits of the new species, we hypothesize that the new species is also bee-pollinated.…”
Section: Taxonomymentioning
confidence: 89%
“…Pollination ecology:-A recent comparative study of floral morphology and pollination ecology demonstrated that the closely related and morphologically similar I. daraneenae, is pollinated by bees (Ruchisansakun et al 2016). The presence of a large floral chamber with a wide entrance are traits associated with bee pollination in Southeast Asian Impatiens (Ruchisansakun et al 2016).…”
Section: Taxonomymentioning
confidence: 99%
“…This prediction is based on the strong similarity in floral features, including flower size, between I. decurva and I. muscicola. For the latter species autonomous self-pollination was experimentally confirmed (Ruchisansakun et al 2016). Phenology:-Flowering and fruiting in September.…”
Section: Distribution:-endemic To Myanmar (Shan State)mentioning
confidence: 91%
“…However, based on the possession of a long, broad spur, we predict that this species is pollinated by both bees and butterflies (cf. Ruchisansakun et al 2016). Proposed IUCN conservation assessment:-Critically Endangered B1ab (i, ii, iii).…”
Section: Distribution:-endemic To Myanmar (Rakhine State)mentioning
confidence: 99%